Palladacyclopentadienyl complexes bearing purine‐based N‐heterocyclic carbenes: A new class of promising antiproliferative agents against human ovarian cancer. (19th March 2019) - Scattolin, Thomas; Giust, Sonia; Bergamini, Paola; Caligiuri, Isabella; Canovese, Luciano; Demitri, Nicola; Gambari, Roberto; Lampronti, Ilaria; Rizzolio, Flavio; Visentin, Fabiano
Abstract : A complete protocol for the synthesis of new palladacyclopentadienyl complexes with purine‐based carbenes as supporting ligands is described. The new organometallic compounds were exhaustively characterized using NMR and infrared spectroscopies and elemental analysis. The single‐crystal X‐ray structure of complex2b coordinating also a triphenylphosphine was resolved. Some of these complexes showed an antiproliferative activity comparable to or better than that of cisplatin on two human ovarian cancer lines: A2780 (cisplatin‐sensitive) and A2780cis (cisplatin‐resistant). Moreover, for complexes2 and3 (coordinating one purine‐based N‐heterocyclic carbene ligand and one phosphine) the cytotoxicity is associated with an evident induction of apoptosis. Finally, complexes3, bearing one purine‐based N‐heterocyclic carbene ligand and one 1, 3, 5‐triaza‐7‐phosphaadamantane, proved practically inactive on non‐tumour fibroblast cells (MRC‐5). Abstract : New palladium complexes bearing purine‐based carbenes have been synthesized and their antiproliferative and pro‐apoptotic activities have been investigated against two human ovarian cancer cell lines. Several compounds show cytotoxicity comparable to that of cisplatin, induce apoptosis and are selective against tumour cells.